2017
DOI: 10.1161/jaha.117.005562
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor and Eptifibatide Bolus Versus Ticagrelor and Eptifibatide Bolus With 2‐Hour Infusion in High‐Risk Acute Coronary Syndromes Patients Undergoing Early Percutaneous Coronary Intervention

Abstract: BackgroundIn patients with non‐ST‐segment elevation acute coronary syndromes, inhibition of platelet aggregation (IPA) with a potent P2Y12 inhibitor, ticagrelor, was inferior to tirofiban infusion at 2 hours, indicating that glycoprotein IIb/IIIa inhibitors are still needed. Ticagrelor and eptifibatide bolus only may maximally inhibit platelet aggregation and decrease bleeding, but IPA with ticagrelor and eptifibatide bolus versus 2‐hour infusion is unknown.Methods and ResultsA total of 70 P2Y12‐naïve patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…19 Obtaining the effective dosage of eptifibatide is essential for the appropriate use of the drug. 1 Herein, we investigated the PK profile of eptifibatide and its antiplatelet aggregation in healthy Chinese subjects for the rational use of eptifibatide in the clinic. Compared with the previous studies that included healthy subjects from California, 14,20,21 the CL was slightly higher in Chinese subjects (112 mL/min for Chinese vs 95 mL/min for US subjects) and the volume of distribution (24 L for Chinese vs 20-22 L for US subjects) was similar.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…19 Obtaining the effective dosage of eptifibatide is essential for the appropriate use of the drug. 1 Herein, we investigated the PK profile of eptifibatide and its antiplatelet aggregation in healthy Chinese subjects for the rational use of eptifibatide in the clinic. Compared with the previous studies that included healthy subjects from California, 14,20,21 the CL was slightly higher in Chinese subjects (112 mL/min for Chinese vs 95 mL/min for US subjects) and the volume of distribution (24 L for Chinese vs 20-22 L for US subjects) was similar.…”
Section: Discussionmentioning
confidence: 99%
“…The platelet GPIIb‐IIIa antagonist eptifibatide can prevent death or myocardial infarctions in patients with ACS and PCI . Obtaining the effective dosage of eptifibatide is essential for the appropriate use of the drug . Herein, we investigated the PK profile of eptifibatide and its antiplatelet aggregation in healthy Chinese subjects for the rational use of eptifibatide in the clinic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although most studies have reported that bolus only or with short duration has similar outcome with lower rate of bleeding, our study did not show significant difference in MACE or bleeding rate between groups, although the rate was lower in bolus only group. However, Marian et al [ 20 ] evaluated the efficacy of ticagrelor and eptifibatide bolus versus ticagrelor and eptifibatide bolus with 2-h infusion in high-risk acute coronary syndrome (ACS) patients undergoing early PCI and observed that the maximum platelet aggregation inhibition was achieved at 2 h, with no significant bleeding indicative of the need for eptifibatide 2-h infusion. Regarding the literature, there is still need for further study to evaluate the exact dosage and protocol of eptifibatide infusion in patients undergoing elective PCI.…”
Section: Discussionmentioning
confidence: 99%